A comparative pharmacokinetics study of Ashwagandha (Withania somnifera) Root Extract sustained-release capsules: an open-label, randomized, two treatment, two-sequence, two period, single-dose crossover clinical study - Alluri, Venkata Krishna Raju; Thanawala, Shefali; Upadhyay, Vivek (International Journal of Basic & Clinical Pharmacology, 2021)
Background: In this open-label, randomized, balanced, two-treatment, two-sequence, two-period, crossover, single-dose oral comparative pharmacokinetics study, the pharmacokinetics, safety, and tolerability of test product ‘ashwagandha (Withania somnifera)’ root extract sustained release capsule 300 mg (Prolanza™), each containing 15 mg withanolides (administered dose: 2×15 mg) was compared with that of a reference product (organic KSM-66 ashwagandha extract [vegan] capsule, each containing 15 mg withanolides [administered dose: 2×15 mg]). Methods: Total 14 healthy men were randomized to receive either the test or the reference product as a single dose of 2 capsules in sequence, administered under fasting conditions. Plasma concentrations of total withanolides, withanolide A and 12-deoxywithastramonolide were measured using validated liquid chromatography–mass spectroscopy/mass spectroscopy. Results: The test product had higher relative absorption, better relative bioavailability, and longer elimination half-life indicating a sustained-release profile compared to reference. Specifically, the relative bioavailability of the test formulation was 12, 44, and 11 times higher for total withanolides, withanolide A and 12-deoxywithastramonolide, respectively. No adverse events were reported during the study. Conclusions: The sustained-release profile of the test product, compared to reference product, will provide more long-lasting therapeutic effects from a single daily dose (Retrospectively applied on Clinical Trials Registry - India [CTRI]. Application reference number: REF/2020/03/032408). The study reports the unique sustained release formulation of Withania somnifera (Ashwagandha) root extract. The pharmacokinetic study also reports for first time, the successful plasma estimation of withanolide A and 12-deoxywithastraamonolide, the major phytoactives of ashwagandha.